Pharmacy students` perspective of experiential learning in Primary Health Care: the PET-Health/GraduaSUS (Research, Society and Development, 2021)
Objective: The aim with the current study was to understand Pharmacy undergraduates' perspective on experiential learning in Primary Health Care through PET-Health/GraduaSUS project, in a period of two years (2016/2018). Methods: It was a case study, carried out through methods of qualitative research. The study participants were Pharmacy students that took part in the project PET-Health/GraduaSUS from 2016 to 2018. Semi structured interviews were carried out addressing the impact of the project on students` life, positive and negative aspects and suggestions to improve the activity. A content analysis of the data was performed. Results: Five categories emerged from students` reports: Knowledge about the health system, Performance in interprofessional health team, Formation of pharmacist`s professional identity, Proposal and performance of actions addressed to population health needs, Skill to perform actions of health education. Conclusion: The reports suggested that the learning objectives proposed to the Pharmacy students were achieved. The PET-Health/GraduaSUS project enabled the opportunity of formation in an interprofessional context and in health care.